Internal Migration and Sectoral Shift in the Nineteenth-Century United States. Issue 4 (2nd November 2021) - MacDonald, Daniel
Abstract: We study the relationship between internal migration and industrialization in the United States between 1850 and 1880. We use the Linked Representative Samples from IPUMS and find significant amounts of rural-urban and urban-urban migration in New England. Rural-urban migration was mainly driven by agricultural workers shifting to manufacturing occupations. Urban-urban migration was driven by foreign-born workers in manufacturing. We argue that rural-urban migration was a significant factor in US economic development and the structural transformation from agriculture to manufacturing.